Pengaruh Jenis Humidifier (Spray Humidifier dan Pad Humidifier)Terhadap Produktivitas Unit Desalinasi Berbasis Pompa Kalor Dengan Menggunakan Proses Humidifikasi dan Dehumidifikasi - Indri Yaningsih; Tri Istanto (JURNAL MECHANICAL, 2015)
This research examined the effect of the use of spray humidifier and pad humidifier on the productivity of a desalination unit based heat pump with using humidification and dehumidification process. In spray humidifier there were 5 pieces of sprinklers for spraying sea water. In pad humidifier, sea water was distributed evenly over the top by means of sea water flowing through perforated pipes that have been placed on pad humidifier. Tested the effect of sea water volumetric flow rate, air velocity and sea water temperature which was fed to spray humidifier and pad humidifier on the fresh water production resulted from desalination unit.The research result showed that the production of fresh water increased with the increase in the sea water volumetric flow rate, air velocity, and sea water temperature, this applies to the use of spray humidifier or pad humidifier in the desalination unit.On testing of the effect of the sea water volumetric flow rate, air velocity, and sea water temperature, the performance of spray humidifier and pad humidifier was equal in the production of fresh water, when the ratio of sea water mass flow rate to air mass flow rate of 1.34, 1.3 and 1.3, respectively.Keywords : dehumidification,desalination, humidification, pad humidifier, spray humidifier